2017
DOI: 10.1016/j.ijbiomac.2016.12.076
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/sulfated locust bean gum nanoparticles: In vitro and in vivo evaluation towards an application in oral immunization

Abstract: This work proposes the design of nanoparticles based on locus bean gum (LBG) and chitosan to be used as oral immunoadjuvant for vaccination purposes. LBG-based nanoparticles were prepared by mild polyelectrolyte complexation between chitosan (CS) and a synthesized LBG sulfate derivative (LBGS). Morphological characterization suggested that nanoparticles present a solid and compact structure with spherical-like shape. Sizes around 180-200nm and a positive surface charge between +9mV and +14mV were obtained. CS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Drug-loaded LBG microparticles had stronger impact in released LDH ( Figure 5) compared with the effect on mitochondrial dehydrogenase activity assessed in MTT assay ( Figure 4B). Other studies report similar observations (Braz et al, 2017;Wang et al, 2009) and several justifications may apply. In fact, the two assays evaluate different aspects of the interaction between cells and particles.…”
Section: In Vitro Cytotoxicity Of Lbg Microparticlesmentioning
confidence: 53%
“…Drug-loaded LBG microparticles had stronger impact in released LDH ( Figure 5) compared with the effect on mitochondrial dehydrogenase activity assessed in MTT assay ( Figure 4B). Other studies report similar observations (Braz et al, 2017;Wang et al, 2009) and several justifications may apply. In fact, the two assays evaluate different aspects of the interaction between cells and particles.…”
Section: In Vitro Cytotoxicity Of Lbg Microparticlesmentioning
confidence: 53%
“…Cytotoxicity test on Caco-2 cells were performed by MTT conversion assay (Braz et al, 2017;Ren et al, 2018), according to Tibolla et al (2019) procedure. Briefly, β-Lg micro-(24 × 10 −3 to 13.5 mg mL −1 ), nanostructures (1 -4.5 mg mL −1 ), β-Lg micro-and nanostructures associated to riboflavin (21 × 10 −3 to 94.5 × 10 −3 mg mL −1 riboflavin), β-Lg micro-and nanostructures associated to quercetin (0.128 × 10 −3 to 40 × 10 −3 mg mL −1 quercetin), free bioactive model compounds and ethanol (in equivalent quercetin concentrations) were diluted in supplemented DMEM medium and homogenized.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…In 2017, Sarmento et al. synthesized sulfated LBG with SO 3 ⋅ DMF complex and reported, for the first time, the production of nanoparticles through complexation with chitosan by means of an electrostatic interaction . The studies further indicated that chitosan/LBG sulfate nanoparticles were promising for the development of an antigen delivery strategy.…”
Section: Biomedical and Bioengineering Applications Of Artificially Smentioning
confidence: 99%
“…In addition to CS and CHS, there are also sulfates of af ew other polysaccharides, such as starch sulfate, dextran sulfate, pullulan sulfate, sulfated LBG, and heparosan sulfate, that can act as GAG analogues in biomedical fields. [96][97][98][99][100][101][102][103][104][105][106][107][108] These diverse GAG analogues can be synthesized through versatile synthetic methods (Scheme 3). [96][97][98][99][100][101][102][103][104][105][106][107][108] The chemical structuresc an be determined through various methods,i ncluding FTIR, FT Raman, NMR spectroscopy,and elemental analysis.…”
Section: Sulfates Of Other Polysaccharidesmentioning
confidence: 99%